Association between NOTCH3 gene and Parkinson’s disease based on whole-exome sequencing - Zeng, Qian; Pan, Hongxu; Zhao, Yuwen; Wang, Yige; Xu, Qian; Tan, Jieqiong; Yan, Xinxiang; Li, Jinchen; Tang, Beisha; Guo, Jifeng (Frontiers in Aging Neuroscience, 2022)
Objective: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a hereditary cerebral small vessel disease caused by mutations in the NOTCH3 gene. Previous studies have established a link between NOTCH3 variants and Parkinson’s disease (PD) in terms of neuropathology and clinical characteristics. In this study, we aimed to explore the role of NOTCH3 gene in PD in a large Chinese cohort. Methods: A total of 1,917 patients with early-onset or familial PD and 1,652 matched controls were included. All variants were divided into common or rare types by minor allele frequency (MAF) at a threshold of 0.01 (MAF > 0.01 into common variants and others into rare variants). Common variants were subjected to single-variant tests by PLINK, then gene-based analyses were used for rare variants with the optimized sequence kernel association test (SKAT-O). For genotype-phenotype correlation assessment, regression models were conducted to compare clinical features between the studied groups. Results: Three common variants (rs1044006, rs1043997, and rs1043994) showed a nominal protective effect against PD. However, none of these SNPs survived Bonferroni correction. The results in the validation cohort revealed a significant but opposite association between these variants and PD. The gene-based analyses of rare variants showed no significant associations of NOTCH3 with PD. Although we did not find significant associations in the following genotype-phenotype analysis, the higher clinical scores of motor symptoms in NOTCH3-variant carriers were of interest. Conclusion: Our results indicated that NOTCH3 gene may not play an important role in the early-onset or familial PD of Chinese population.